The Effect of Price, Taste Experience, Viral Marketing Activity, and E-Word of Mouth on Customer Satisfaction and Brand Loyalty on Mixue Products - Chandra, Priscillia; Ardi, Ardi; Berlianto, Margaretha Pink (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study aims to examine the influence of Price, Taste Experience, Viral Marketing Activity, and Electronic Word of Mouth (E-WoM) on Customer Satisfaction, as well as its subsequent impact on Brand Loyalty. The research was conducted on Mixue consumers in the Jabodetabek area, involving 149 respondents selected through purposive sampling, a type of non-probability sampling technique. The research model and its hypotheses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected via an online questionnaire distributed through Google Forms, consisting of 32 Likert-scale statements (1–5). The findings indicate that while Price has a positive but statistically insignificant effect on Customer Satisfaction, Taste Experience, Viral Marketing Activity, and E-WoM each have a positive and significant influence. Based on these results, it is recommended that Mixue enhance customer satisfaction by developing more localized and innovative taste offerings and conducting regular flavor testing to meet consumer preferences. Additionally, viral marketing efforts can be optimized by encouraging user-generated content and collaborating with micro-influencers to strengthen engagement and emotional connection with the brand.